Shades of Grace: The Virgin of the Rocks and Leonardo da Vinci’s Notes on Paragone - De Mambro Santos, Ricardo (Religions, 2021)
This essay analyses Leonardo da Vinci’s innovative iconography in the making of the panel known as the Virgin of the Rocks (Paris, Louvre) in relation to his considerations on the important Renaissance debate of Paragone, or comparison among the arts, namely, Painting, Sculpture, Music, and Poetry. It will be argued that this work, as a depiction of a complex religious theme, may be interpreted as a laboratory for Paragone-related demonstrations, especially in regards to five points: the optical tangibility of the image; the temporalities involved in the representation; the variety of subjects; and, finally, its iconic stability and semiotic openness as vehicles to further stimulate the devotional value of the painting.